A dynamic-based method for the assessment of connection systems of timber composite structures. (15th January 2016) - Dackermann, Ulrike; Li, Jianchun; Rijal, Rajendra; Crews, Keith
Highlights: Vibration measurements for the integrity assessment of shear connectors in composite systems. Dynamic-based testing and analysis to provide a good alternative to static load tests. Experimental and numerical study of timber composite systems. The method allows the use of a few mode measurements without compromising good results. Abstract: This paper presents a dynamic-based method for the evaluation of connection systems of timber composite structures. The good bonding of the composite elements is crucial for the proper functioning of timber composite structures, as the design capacity and performance of the system cannot be achieved unless an adequate connection condition can be assured. The proposed dynamic method provides an alternative to traditional static load testing and uses vibration measurements to derive a Loss of Composite Action Index, based on an expanded Damage Index method, indicating the reduction in composite action due to the failure of shear connectors. The proposed method is validated on experimental and numerical models of a timber composite beam structure and a timber-concrete composite flooring system. The results demonstrate the effectiveness of the proposed dynamic-based approach that can achieve a good agreement between statically and dynamically derived composite action indicators.